2019
DOI: 10.1002/adfm.201902634
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles for Drug Delivery

Abstract: In recent years, nanomedicine has emerged at the forefront of nanotechnology area generating great expectations in the biomedical field. Researchers are developing novel nanoparticles for both diagnostic applications using imaging technology and treatment purposes through drug delivery technologies. Among all the available nanoparticles, inorganic mesoporous silica nanoparticles are the newcomers to the field contributing with their unique and superlative properties. In this Progress Report we provide a brief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
367
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 677 publications
(430 citation statements)
references
References 162 publications
2
367
0
12
Order By: Relevance
“…For instance, it has been shown in vivo that the larger the nanoparticles the faster their excretion [84]. In addition, it has been observed that, unlike spherical particles, those presenting elongated or cylindrical shapes undergo faster clearance from the bloodstream [85]. Finally, the surface charge is a key parameter since it determines the interaction of the particles with the surrounding media.…”
Section: Biodistribution and Biodegradation Of Mesoporous Silica Nanomentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown in vivo that the larger the nanoparticles the faster their excretion [84]. In addition, it has been observed that, unlike spherical particles, those presenting elongated or cylindrical shapes undergo faster clearance from the bloodstream [85]. Finally, the surface charge is a key parameter since it determines the interaction of the particles with the surrounding media.…”
Section: Biodistribution and Biodegradation Of Mesoporous Silica Nanomentioning
confidence: 99%
“…The dissolution rate depends on the particular characteristics of the particles and can be tuned through the introduction of organic modifications on the surface. Those modifications have been shown not to affect the biodistribution and biocompatibility of the MSNs [85].…”
Section: Biodistribution and Biodegradation Of Mesoporous Silica Nanomentioning
confidence: 99%
“…Moreover, to combine great mechanical strength and excellent bioactivity of BGs, they can be successfully used as coatings on inert substrates [82]. Reaction to the physiological fluids and the formation of chemical bonding between bones and bioglass can be occurred when bioglasses are implanted in the body [83][84][85][86][87]. A bioactive surface can be considered as important agent to avoid many simultaneous reactions, which take place between the implant and the targeted tissue at the implant surface [82].…”
Section: Bioactive Glass In Biomedical Applicationsmentioning
confidence: 99%
“…PMONPs are synthesized from trialkoxypolysilylated organic precursors and usually silica sources are not used for their preparation. PMONPs possess improved properties compared to Mesoporous Silica Nanoparticles (MSN), which have been considerably reported for their nanomedicine applications [5][6][7][8][9][10][11][12]. Indeed, PMONPs can be loaded with hydrophobic or hydrophilic molecules and present better hemolytic properties than MSN [13,14].…”
Section: Introductionmentioning
confidence: 99%